Synthesis and Crystal Structure of New (3,5)-Connected Ni(II) Coordination Polymer - Chu, Zepeng; Zhao, Minghui (Asian Journal of Chemistry, 2014)
In this paper, a new Ni(II) coordination polymer with 3,4-pyridine dicarboxylic acid(3, 4-PDB) and 1,4-bis (1-imidazol-yl)-2,5-dimethyl benzene (bimb) has been prepared by hydrothermal synthesis and characterized by single-crystal X-ray diffraction, IR and EA. Complex, [Ni(3, 4-PDB)(bimb)(H2O)]n (1), is monoclinic, space group P21/c with a = 10.254 (5), b = 14.219(5), c = 14.288 (5)Å, b = 100.816 (5)°, V = 2046.2(14)Å3, Z = 4, Mr = 480.12, Dc =1.559 g/cm3 and F(000) = 992. The final refinement gave R = 0.0285 and wR = 0.0800 for 4205 reflections with I > 2s(I). X-ray diffraction analysis reveals that the complex 1 displays a new three-dimensional structure with a (3,5)-connected topology.